PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DI JOVANBEAUTY - Myechael Siregar; Syifa Pramudita Faddilla (PT Naureen Digital Education, 2023)
Motivating employees is crucial for enhancing their productivity and overall organizational success. This study utilized qualitative interviews to gather data. The qualitative phase included in-depth interviews with key employees to gain insights into the motivating factors and challenges they face. The findings revealed a positive relationship between employee motivation and performance atJovanBeauty. The qualitative analysis uncovered key motivational factors, including recognition and appreciation, career development opportunities, and a positive and inclusive work environment. Additionally, the qualitative analysis identified challenges such as lack of management support, work fatigue, and limited participation in decision-making processes. The implications suggest that JovanBeauty needs to focus on enhancing employee motivation to improve performance. This can be achieved through effective motivation programs that recognize employees' achievements, offer clear career development paths, and create a positive work environment. Addressing the identified challenges by improving communication, managing workload effectively, and involving employees in decision-making processes can further enhance